Assessment of 3D earthquake response of the Arhavi Highway Tunnel considering soil-structure interaction - Sevim, Baris (TECHNO-PRESS, 2013)
This paper describes earthquake response of the Arhavi Highway Tunnel its geometrical properties, 3D finite element model and the linear time history analyses under a huge ground motion considering soil-structure interaction. The Arhavi Highway Tunnel is one of the tallest tunnels constructed in the Black Sea region of Turkey as part of the Coast Road Project. The tunnel has two tubes and each of them is about 1000 m tall. In the study, lineartime history analyses of the tunnel are performed applying north-south, east-west and up accelerations components of 1992 Erzincan, Turkey ground motion. In the time history analyses, Rayleigh damping coefficients are calculated using main natural frequency obtained from modal analysis. Element matrices are computed using the Gauss numerical integration technique. The Newmark method is used in the solution of the equation of motion. Because of needed too much memory for the analyses, the first 10 second of the ground motions, which is the most effective duration, is taken into account in calculations. The results obtained 3D finite element model are presented. In addition, the displacement and stress results are observed to be allowable level of the concrete material during the earthquakes.
Keywords: earthquake response; linear time history analysis; highway tunnel; soil-structure interaction; 3D FEM; Computer Science; Construction & Building Technology; Engineering; Materials Science